Exploring the Impact of Corporate Governance, Organizational Commitment, and Tri Hita Karana Culture on Financial Performance (E-Jurnal Akuntansi, 2026)
The objective of this study is to assess the effects of Good Corporate Governance (GCG) Principles, Organizational Commitment, and Tri Hita Karana (THK) Culture on the financial performance of Lembaga Perkreditan Desa (LPD) in Karangasem Regency. The research includes a population of 190 LPDs in Karangasem Regency, using a purposive sampling method to select 20 LPDs. Data were collected through questionnaires distributed to respondents holding the roles of Pemucuk and Panureksa at these LPDs. Multiple linear regression analysis was employed to analyze the data. The findings reveal that GCG Principles, Organizational Commitment, and THK Culture positively affect the financial performance of LPDs, suggesting that enhancing these factors can significantly improve financial outcomes across LPDs in Karangasem Regency.
Keywords: Organizational Commitment; Tri Hita Karana Culture; Financial Performance; Good Corporate Governance Principles